Implementasi Prinsip-Prinsip Good Governance Dalam Meningkatkan Kualitas Pelayanan Publik (Studi Kasus Pada Sekretariat DPRD Kota Malang) - Andhini, Shanti Yuka; Wahyudi, Sigit; Khannanah, Sulafah Fathin (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
(the problem of implementing the principles of good governance in improving the quality of public services in the Registrar Office of the Malang City DPRD. This matter is framed by the strong insistence on democracy and the recognition of the basic rights of people which gave birth to pressure for quality public service management, which is regime (good governance). To achieve this goal, it is necessary to be assisted by human resources who are qualified, reliable, have understanding and are able to provide good services to the community. This research aims to identify how the application of the principles of good governance in improving service quality the public at the Registrar Office of the Malang City DPRD acts like a colleague for the activities of the Malang City authorities. The procedure used in this research is a qualitative research procedure. A qualitative procedure describes information based on facts, information and data directly from research positions. The method of collecting information uses in-depth debriefing (in deep interview) and assisted by monitoring and selection methods. The results of the research confirm that the application of the principles of good governance in the Registrar's Office of the Malang City DPRD has been running quite well, although there are still some deficiencies that need to be corrected and by implementing the principles of good governance in the Registrar's Office of the Malang City DPRD, it has succeeded in increasing the quality of public services in that body. . Not only improving the quality of public services, the application of the principles of good governance also has positive consequences for various parties who participate, including civil servants for the clerkship of the Malang City DPRD and ordinary citizens acting like consumers of public services for the clerkship of the Malang City DPRD.